"Visiting Day" at Rikers Island. Issue 2 (3rd July 2018) - Shanahan, Jarrod
ABSTRACT: Wacquant (2002) calls for ethnography to meet the jailhouse on its own terms, noting the dearth of first-hand writing from the carceral facility. This article describes a creative representation of qualitative research made by the author and two creative collaborators that both meets Wacquant's call and problematizes it; meets it, as we depict the functioning of the visitation process at Rikers Island based on our first-hand experience on both sides of the bars, and problematizes it, as we chose for our medium the zine, a creative form common to prison writing, yet not sufficiently academic by Wacquant's standards. I offer a novel definition of the zine form grounded in the academic literature, describe the visitation process at Rikers and the making of the "Visiting Day" zine, and reflect on challenges to the binary of inside/outside the carceral facility, as well as the political stakes of this theoretical formulation.